Edukasi Kesehatan tentang Faktor Penyebab Kecemasan Ibu Hamil Trimester III Sebagai Upaya dalam Persiapan Persalinan - Herlina, Siskha Maya; Yopi Suryatim Pratiwi; Regina Pricilia Yunikar; Yadul Ulya (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Pregnancy is a significant moment in a woman's life, a time of great joy and hope. However, pregnancy can also be a challenging and stressful time, both physically and emotionally. This condition often becomes an emotional crisis for some women and, if not managed properly, can lead to complications for both mother and baby. Evidence shows that various somatic and psychological problems, such as fear, anxiety, and depression, often accompany pregnancy. Anxiety is a mental state often characterized by feelings of worry, dread, and anxiety about things that have not yet happened or may happen in the future, including high risks for the pregnant woman. Pregnant women with a history of miscarriage may fear that they will lose another baby, and this can exacerbate their anxiety. Anxiety that persists throughout the labor process can prolong labor and increase the risk of maternal and fetal death. Therefore, a community service initiative in Jempong Baru District was carried out to increase the knowledge of pregnant women in the third trimester to find out the factors that cause anxiety before childbirth as an effort to prepare for a healthy childbirth. Using a lecture method supported by audiovisual media and leaflets, this program follows the stages of pre-test, counseling, and post-test, which showed a significant increase in the knowledge of pregnant women in the third trimester from 16% in the good category to 80% after the intervention. This program and activity not only increase the knowledge of pregnant women but prepares for childbirth to be safer and well-planned, thereby reducing anxiety before childbirth.